Relación del lenguaje corporal en la formación integral de los profesionales en Comunicación Social del cantón El Empalme, año 2022 - Tello Toala, Giselda Karina (2022)
This research addressed the issues of body language and comprehensive training, for professionals in charge of distributing information, such as social communicators, it is essential that they handle these tools. The objective is to analyze the incidence of the relationship of body language in the comprehensive training of communication professionals in the El Empalme canton, year 2021. The technique used is the online survey using the questionnaire instrument in Google forms. This case study shows that the professional in social communication needs to know body expressions, be trained, create a training plan and thus contribute to the development of the professional field, in the assessment of knowledge through various techniques that promote discovering, expanding as much as possible. internal or deep in the body.